2014
DOI: 10.1590/s0004-28032014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy and Carcinoembryonic Antigen Variations

Abstract: Context Colonoscopy is essential for synchronous and metachronous cancer detection. Carcinoembryonic antigen is a colorectal cancer tumor marker, important as a follow-up tool in patients with previous colorectal cancer. False-positive carcinoembryonic antigen elevation results in multiples exams and in patient anxiety. In literature, there is reference to transient carcinoembryonic antigen increase with colonoscopy. Objective To evaluate the influence of bowel preparation and colonoscopy in carcinoembryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Tumour markers are known to increase in serum during invasive procedures targeting the tumoral tissue (endoscopy, biopsy, etc 16,17 ) or during treatment (chemotherapy 18,19 ). Serum TG is the primary tumour marker used to monitor for residual or recurrent disease in DTC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour markers are known to increase in serum during invasive procedures targeting the tumoral tissue (endoscopy, biopsy, etc 16,17 ) or during treatment (chemotherapy 18,19 ). Serum TG is the primary tumour marker used to monitor for residual or recurrent disease in DTC patients.…”
Section: Introductionmentioning
confidence: 99%
“…When conducting a thorough literature search (PubMed and EMbase) only a few reports exist, most of which concern the well-described and well-established biomarker Carcinoembryonic Antigen (CEA). One study found no effect of bowel preparation 28 , yet two other studies found a small increase in serum CEA after bowel preparation 29,30 . Thus, CEA levels appear to show limited variations of what might be expected from preanalytical-, analytical-and biological variation.…”
Section: Introductionmentioning
confidence: 99%
“…33 Sousa et al have reported false positive elevation of CEA after bowel cleaning. 34 Previously a physiologically expressed CEA splice variant has been identified. 35 As in our case it has been previously reported to be another important situation to be remembered in false positive elevation of CEA is uremia and renal failure.…”
mentioning
confidence: 99%